2009
DOI: 10.1182/blood-2008-11-187708
|View full text |Cite
|
Sign up to set email alerts
|

Nutlin-3 up-regulates the expression of Notch1 in both myeloid and lymphoid leukemic cells, as part of a negative feedback antiapoptotic mechanism

Abstract: The small molecule inhibitor of the MDM2/ p53 interaction Nutlin-3 significantly upregulated the steady-state mRNA and protein levels of Notch1 in TP53 wild-type (OCI, SKW6.4) but not in TP53 deleted (HL-60) or TP53 mutated (BJAB) leukemic cell lines. A direct demonstration that NOTCH1 was a transcriptional target of p53 in leukemic cells was obtained in experiments carried out with siRNA for p53. Moreover, inhibition of Notch1 expression using Notch1-specific siRNA significantly increased cytotoxicity in TP53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 48 publications
3
61
0
Order By: Relevance
“…Beverly and colleagues observed suppression of Trp53 levels by NICD1 and suggested that this might reflect Mdm2-dependent events (Beverly et al, 2005). Secchiero and colleagues (Secchiero et al, 2009) found that, in cells lacking active Trp53, Notch1 protein levels were stable in the presence or absence of the Mdm2 and Trp53 inhibitor Nutlin, consistent with the notion that binding of Trp53 to Notch 1 is important for Mdm2-mediated degradation of Notch1.…”
Section: Discussionsupporting
confidence: 49%
“…Beverly and colleagues observed suppression of Trp53 levels by NICD1 and suggested that this might reflect Mdm2-dependent events (Beverly et al, 2005). Secchiero and colleagues (Secchiero et al, 2009) found that, in cells lacking active Trp53, Notch1 protein levels were stable in the presence or absence of the Mdm2 and Trp53 inhibitor Nutlin, consistent with the notion that binding of Trp53 to Notch 1 is important for Mdm2-mediated degradation of Notch1.…”
Section: Discussionsupporting
confidence: 49%
“…Besides the key role of NOTCH2 in CLL, NOTCH1 gain of function mutations are found in a small group of CLL patients (Fabbri et al, 2011;Puente et al, 2011). NOTCH1 has been identified as a direct target gene of TP53 and might counteract the apoptotic effect of TP53 in CLL cells (Secchiero et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…An intriguing link between p53 and the Notch 1 pathway has been revealed in a study by Secchiero et al 27 Treatment of primary CLL cells with nutlin 3 resulted in elevation of both p53 and Notch 1. Furthermore, g-secretase inhibitors, which block the generation of the active Notch proteins (Figure 2), augmented the cytotoxicity of nutlin 3, compatible with the interpretation that induction of Notch 1 expression by p53 initiated an antiapoptotic feedback mechanism that limited the cytotoxic actions of nutlin 3.…”
Section: Notch 1 As a Potential Antiapoptotic P53 Targetmentioning
confidence: 99%
“…24 The Notch signaling pathway Recent evidence suggests that the Notch signaling pathway is a downstream target of p53. 25 The p53/Notch interaction may account for some recent observations in CLL cells, 26,27 which are described in detail below. We therefore review briefly the molecular regulation of the Notch pathway.…”
Section: Transcriptional Targets Of P53mentioning
confidence: 99%
See 1 more Smart Citation